Предмет: Математика,
автор: кошка446
решите уравнение (х+3)(х-4)=(х+3)(5х+14)
Ответы
Автор ответа:
0
(х+3)(х-4) = (х+3)(5х+14),
х² + 3х - 4х - 12 = 5х² + 14х + 15х + 42,
х² - х - 12 = 5х² + 29х + 42,
х² - 5х² - х - 29х - 12 - 42 = 0,
-4х² - 30х - 54 = 0,
2х² + 15х + 27 = 0,
Д = 15² - 4*2*27 = 225 - 216 = 9,
х1 = (-15+3)/2*2 = -12/4 = -3,
х2 = (-15-3)/2*2 = -18/4 = -4,5 (или -4 1/2)
х² + 3х - 4х - 12 = 5х² + 14х + 15х + 42,
х² - х - 12 = 5х² + 29х + 42,
х² - 5х² - х - 29х - 12 - 42 = 0,
-4х² - 30х - 54 = 0,
2х² + 15х + 27 = 0,
Д = 15² - 4*2*27 = 225 - 216 = 9,
х1 = (-15+3)/2*2 = -12/4 = -3,
х2 = (-15-3)/2*2 = -18/4 = -4,5 (или -4 1/2)
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: Alisa123www
Предмет: История,
автор: katya20101077
Предмет: Биология,
автор: katyadinner